Kunkecin A, a New Nisin Variant Bacteriocin Produced by the Fructophilic Lactic Acid Bacterium, Apilactobacillus kunkeei FF30-6 Isolated From Honey Bees - Zendo, Takeshi; Ohashi, Chihiro; Maeno, Shintaro; Piao, Xingguo; Salminen, Seppo; Sonomoto, Kenji; Endo, Akihito (Frontiers in Microbiology, 2020)
Apilactobacillus kunkeei FF30-6 isolated from healthy honey bees synthesizes the bacteriocin, which exhibits antimicrobial activity against Melissococcus plutonius. The bacteriocin, kunkecin A, was purified through three-step chromatography, and mass spectrometry revealed that its relative molecular mass was 4218.3. Edman degradation of purified kunkecin A showed only the N-terminal residue, isoleucine. Hence, alkaline alkylation made the subsequent amino acid residues accessible to Edman degradation, and 30 cycles were sequenced with 11 unidentified residues. Whole genome sequencing of A. kunkeei FF30-6, followed by Sanger sequencing, revealed that the genes encoding the proteins involved in lantibiotic biosynthesis were within the plasmid, pKUNFF30-6. Most of the identified proteins exhibited significant sequence similarities to the biosynthetic proteins of nisin A and its variants, such as subtilin. However, the kunkecin A gene cluster lacked the genes corresponding to nisI, nisR, and nisK of the nisin A biosynthetic gene cluster. A comparison of the gene products of kukA and nisA (kunkecin A and nisin A structural genes, respectively) suggested that they had similar post-translational modifications. Furthermore, the structure of kunkecin A was proposed based on a comparison of the observed and calculated relative molecular masses of kunkecin A. The structural analysis revealed that kunkecin A and nisin A had a similar mono-sulfide linkage pattern. Purified kunkecin A exhibited a narrow antibacterial spectrum, but high antibacterial activity against M. plutonius. Kunkecin A is the first bacteriocin to be characterized in fructophilic lactic acid bacteria and is the first nisin-type lantibiotic found in the family Lactobacillaceae.